2007
DOI: 10.1182/blood-2007-04-085969
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of allogeneic hematopoietic stem-cell transplantation with reduced-intensity conditioning for patients with chronic myeloid leukemia

Abstract: Allogeneic hematopoietic stem-cell transplantation (HSCT) remains an effective strategy for inducing durable remission in chronic myeloid leukemia (CML). Reduced-intensity conditioning (RIC) regimens extend HSCT to older patients and those with comorbidities who would otherwise not be suitable candidates for HSCT. The long-term efficacy of this approach is not established. We evaluated outcomes of 64 CML patients with advanced-phase disease (80% beyond first chronic phase), not eligible for myeloablative prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 32 publications
1
30
0
Order By: Relevance
“…[16][17][18]44 Notably, the addition of TMLI to FLU/MEL does not appear to increase toxicity over that seen with FLU/MEL conditioning regimen alone, based on previous results from our institution as well as those reported by other centers. [16][17][18]37,[39][40][41]44 Two patients (6%) died of multiorgan failure, a rate similar to those reported in clinical trials using MEL/FLU without radiation. 18,[45][46][47] Although previous studies have demonstrated a maximal tolerated irradiation dose of 900 cGy in children only, the patients reported here appeared to tolerate TMLI well at 1200 cGy, with the maximal tolerated dose still to be explored.…”
Section: Tmli Augments Reduced-intensity Transplantation 313supporting
confidence: 58%
See 1 more Smart Citation
“…[16][17][18]44 Notably, the addition of TMLI to FLU/MEL does not appear to increase toxicity over that seen with FLU/MEL conditioning regimen alone, based on previous results from our institution as well as those reported by other centers. [16][17][18]37,[39][40][41]44 Two patients (6%) died of multiorgan failure, a rate similar to those reported in clinical trials using MEL/FLU without radiation. 18,[45][46][47] Although previous studies have demonstrated a maximal tolerated irradiation dose of 900 cGy in children only, the patients reported here appeared to tolerate TMLI well at 1200 cGy, with the maximal tolerated dose still to be explored.…”
Section: Tmli Augments Reduced-intensity Transplantation 313supporting
confidence: 58%
“…20,37 The significant reduction in intensity of the treatment by RIC may have a negative impact on long-term leukemic control. 16,[37][38][39][40][41] In attempts to improve outcomes, reduced radiation doses of TBI have been added to RIC regimens. Petropoulos et al 21 reported the addition of 900 cGy TBI to standard FLU/MEL in 29 pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with significant gross residual disease probably have too great a tumor burden to benefit from the graft-versus-leukemia effect. 25,26 To date, there have not been published data confirming these results in children. A reduced intensity regimen of busulfan, fludarabine, and rabbit antithymocyte globulin was used in 2 children with CML with success in one recent report.…”
Section: Sct In Pediatric CMLmentioning
confidence: 61%
“…Furthermore, with the increased use of reduced intensity conditioning regimens, 45 additional SNP testing could be used to decide between standard conditioning for patients with a low risk for transplantrelated mortality, reduced conditioning for patients with a high risk for transplant-related mortality, or for delaying HSCT until progression. 46 Additional risk factors have also been clearly established, such as cytomegalovirus serostatus of the recipient, performance score or comorbidity index.…”
mentioning
confidence: 99%